Sleep and Quality of Life in People With COPD: A Descriptive-Correlational Study. (August 2016) - Dignani, Lucia; Toccaceli, Andrea; Lucertini, Carla; Petrucci, Cristina; Lancia, Loreto
Sleep disorders are very common in patients with chronic obstructive pulmonary disease (COPD). However, it is not clear how sleep disorders and quality of life (QoL) affect each other in the different stages of disease progression. This descriptive-correlational study investigated the relationship between QoL, quality of sleep, and degree of disease progression in 102 outpatients with COPD. The results showed that the QoL in patients with COPD is compromised and worsens with disease progression, and the quality of sleep is significantly associated with QoL and worsened as the disease progressed. The early identification of a risk of alteration of the quality of sleep, especially in nursing care, could facilitate a preventive approach for COPD patients that could positively affect their QoL.